Answer:
f(-3) = -1
g(-3) = 14
Step-by-step explanation:
plug -3 for x to get the answer
Answer:
30
Step-by-step explanation:
Answer: ![2x^2+2x-4-\frac{4}{x+1}](https://tex.z-dn.net/?f=2x%5E2%2B2x-4-%5Cfrac%7B4%7D%7Bx%2B1%7D)
Not a factor because there is a remainder.
Step-by-step explanation:
Let's use synthetic division to solve this..
-1 ║ 2 | 4 | -2 | -8
║ | -2| -2 | 4
║ 2 | 2| -4 | -4
![2x^2+2x-4-\frac{4}{x+1}](https://tex.z-dn.net/?f=2x%5E2%2B2x-4-%5Cfrac%7B4%7D%7Bx%2B1%7D)
PS: if anyone knows a better way to do a synthetic division chart please let me know.